2004
DOI: 10.1007/s00253-003-1393-5
|View full text |Cite
|
Sign up to set email alerts
|

Aeration strategy: a need for very high ethanol performance in Saccharomyces cerevisiae fed-batch process

Abstract: In order to identify an optimal aeration strategy for intensifying bio-fuel ethanol production in fermentation processes where growth and production have to be managed simultaneously, we quantified the effect of aeration conditions--oxygen limited vs non limited culture (micro-aerobic vs aerobic culture)--on the dynamic behaviour of Saccharomyces cerevisiae cultivated in very high ethanol performance fed-batch cultures. Fermentation parameters and kinetics were established within a range of ethanol concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
113
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 17 publications
15
113
1
4
Order By: Relevance
“…The addition of glycerol in cultures of strain G175 harboring pESC-URA::cphA 6308 did not result in higher CDM values or polymer contents of the cells. This was also observed for strain G175 and strain BY4741 harboring pYEX-BX::cphA 6308 when they were grown in the presence of two-or fourfold higher concentrations of CuSO 4 . However, HPLC analysis of CGP isolated from cells grown in the presence of 15 mM lysine revealed that this polymer consisted of up to 10 mol% of lysine.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The addition of glycerol in cultures of strain G175 harboring pESC-URA::cphA 6308 did not result in higher CDM values or polymer contents of the cells. This was also observed for strain G175 and strain BY4741 harboring pYEX-BX::cphA 6308 when they were grown in the presence of two-or fourfold higher concentrations of CuSO 4 . However, HPLC analysis of CGP isolated from cells grown in the presence of 15 mM lysine revealed that this polymer consisted of up to 10 mol% of lysine.…”
Section: Resultssupporting
confidence: 57%
“…First, yeast systems that were developed for heterologous gene expression were based on Saccharomyces cerevisiae. This organism is traditionally used for large-scale production of baker's yeast and ethanol, with a considerable increase in the production of fuel ethanol in the last 3 decades (4,6,50). Additionally, this platform has been successfully applied to the production of valuable heterologous proteins on an industrial scale (26,35), such as various FDA-approved pharmaceuticals, including insulin (34) and hepatitis B surface antigen (23).…”
mentioning
confidence: 99%
“…VHG fermentation process exploits the observation that the growth of S. cerevisiae is promoted and prolonged when low levels of oxygen are present and the assimilable nitrogen levels are not limited [16]. The role of a small amount of oxygen supply in improving the ethanol tolerance of yeast cells under a VHG fermentation condition has been discussed [17,18]. Yeast normally requires added oxygen to synthesize lipids (sterols and unsaturated fatty acids), which are essential for plasma membrane integrity [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Providing the adequate amount of aeration during the initial stage of fermentation may reduce the initial yeast cell concentration used and improve the ethanol tolerance of the yeast cells. Alfenore et al [17] reported that aeration at 0.2 vvm led to a 23% increase in the viable cell mass for fed-batch ethanol fermentation, meanwhile the ethanol production and yield were also enhanced. Aeration during the initial stage of yeast growth along with a constant agitation increased the final ethanol concentration from 128.1 g L −1 (without aeration)…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some bioethanol fermentation processes may benefit from mild aeration. 4,27 Under ideal (laboratory-optimised) conditions, S. cerevisiae reproduces quickly (approx. every 90 min), but in industrial fermenters this takes considerably longer due to the stressful physico-chemical environment.…”
Section: Stress Factor Examplesmentioning
confidence: 99%